Penerapan Model Pembelajaran Discovery Learning Pada Mata Pelajaran Creambath Di SMK Negeri 1 Buduran - novita nathania; Octaverina Kecvara Pritasari; Nia Kusstianti; Biyan Yesi Wilujeng (Jurnal Tata Rias, 2025)
The study's three main goals are to: (1) assess how well the discovery learning model syntax was implemented; (2) examine the learning outcomes of the students; and (3) gauge the reactions of the students to the application of the discovery learning model in the creambath class at SMK Negeri 1 Buduran. With its "One Shot Case Study" approach, this study is classified as pre-experimental. Thirty-three students from SMK Negeri 1 Buduran's class X Beauty 2 served as the research subjects. Cognitive tests, questionnaires to gauge student answers, and observation to evaluate the application of the learning syntax were used to gather data. Three research instruments were employed in this study: a student response questionnaire, a cognitive test sheet, and an observation sheet for the syntax's implementation.With an average score of 3.7, the discovery learning model syntax was applied extremely successfully in the learning activities pertaining to the wet scalp and hair care competency (creambath). Students were well-prepared in terms of knowledge based on the conducted learning, as evidenced by the average score of 86.8 for the cognitive learning outcomes following the application of the discovery learning methodology. When expressed as a percentage, the students' responses produced an overall average score of 36.2, or 91%, which is considered extremely good. The findings suggest that students' comprehension has improved, they found the learning model enjoyable, and they found the discovery learning model simpler to understand, especially when it came to the wet scalp and hair care competency (creambath).